Genetic diversity and connectivity of Red Snapper Lutjanus gibbus in the Papua Waters, Indonesia - BAYU PRANATA; RIDWAN SALA; ARADEA BUJANA KUSUMA; ABDUL HAMID A. TOHA; DEBORA CHRISTIN PURBANI; DANIEL FRIKLI MOKODONGAN; SIPRIYADI SIPRIYADI (Society for Indonesian Biodiversity, 2024)
Abstract. Pranata B, Sala R, Kusuma AB, Toha AHA, Purbani DC, Mokodongan DF, Sipriyadi. 2024. Genetic diversity and connectivity of Red Snapper Lutjanus gibbus in the Papua Waters, Indonesia. Biodiversitas 25: 276-286. There is limited knowledge regarding the genetic connectivity and diversity of the Red Snapper (Lutjanus gibbus Forsskål, 1775) populations that inhabit Papua Waters, Indonesia. Thus, the current study attempted to ascertain the genetic characteristics, level of diversity and genetic connectivity of the L. gibbus population. We conducted genetic research on 38 L. gibbus specimens from five different places in Papua Waters. We analyzed the L. gibbus genetic characteristics, diversity and genetic connectivity using the Cytochrome C Oxidase subunit I (COI) gene as the genetic marker. There were 15 polymorphism sites in the COI gene sequence among L. gibbus individuals. Polymorphism occurs due to transversion and transition mutations. The COI gene fragment was translated, producing 188 amino acids composed of 19 different amino acids. A total of 13 distinct haplotypes were detected among the L. gibbus population residing in Papua Waters. The haplotype diversity (Hd=0.740) and nucleotide diversity (Pi=0.002) were relatively medium. The genetic structure study indicated that the 5 populations of L. gibbus in the Papua Waters had little genetic differentiation, as evidenced by a Fixation Index (Fst) of 0.018 (P-value 0.35386±0.01443). Based on this, the management of Red Snapper resources at these 5 locations must be carried out as a single unit.